circSLC41A1 Resists Porcine Granulosa Cell Apoptosis and Follicular Atresia by Promoting SRSF1 through miR-9820-5p Sponging - Huiming Wang; Yi Zhang; Jinbi Zhang; Xing Du; Qifa Li; Zengxiang Pan (2022)
Ovarian granulosa cell (GC) apoptosis is the major cause of follicular atresia. Regulation of non-coding RNAs (ncRNAs) was proved to be involved in regulatory mechanisms of GC apoptosis. circRNAs have been recognized to play important roles in cellular activity. However, the regulatory network of circRNAs in follicular atresia has not been fully validated. In this study, we report a new circRNA, circSLC41A1, which has higher expression in healthy follicles compared to atretic follicles, and confirm its circular structure using RNase R treatment. The resistant function of circSLC41A1 during GC apoptosis was detected by si-RNA transfection and the competitive binding of miR-9820-5p by circSLC41A1 and SRSF1 was detected with a dual-luciferase reporter assay and co-transfection of their inhibitors or siRNA. Additionally, we predicted the protein-coding potential of circSLC41A1 and analyzed the structure of circSLC41A1-134aa. Our study revealed that circSLC41A1 enhanced SRSF1 expression through competitive binding of miR-9820-5p and demonstrated a circSLC41A1-miR-9820-5p-SRSF1 regulatory axis in follicular GC apoptosis. The study adds to knowledge of the post-transcriptional regulation of follicular atresia and provides insight into the protein-coding function of circRNA.